Composition by functional Groups of Contexts at Pompeii - Martin, Archer (Rei Cretariae Romanae Fautorum Acta, 2012)
In an attempt to see how geographic position with respect to trade routes influences the composition of ceramic as-semblages, I compared the percentages for functional groupings (fine ware, lamps, common ware, cooking ware and amphorae) on four 5th-century sites along the Tiber for which I possessed quantified data: Ostia (Casone del Sale), Rome (S. Stefano Rotondo), Lugnano in Teverina (Poggio Gramignano) and Chianciano Terme (Mezzomiglio). The first is, of course, the great port at the mouth of the river; the second the destination of great flows of goods from all around the Mediterranean; the third a site on the navigable stretch of the Tiber above Rome; the fourth a site on a non-navigable tributary of the Tiber. The most evident result of moving upstream was a decrease in the percentage of amphorae from some 2/3 or 3/4 at Ostia and Rome to 1/3 at Lugnano and less than 1/10 at Chianciano. What comparative material was available then suggested that one should expect levels similar to those at Ostia and Rome on Roman Mediterranean sites well integrated into maritime trade networks. Later evidence also supported this – from a 3rd-century context at Rome, where amphorae made up 2/3 of the assemblage, from a 5th-century context at Rome, where amphorae comprise 85.5%; and from Marina el-Alamein, a coastal site in Egypt west of Alexandria dating from the 1st century BC to the end of the 3rd century AD, where amphorae stand at 75–80%.